Coagulation Disorders in Infective Endocarditis: Role of Pathogens, Biomarkers, Antithrombotic Therapy (Systematic Review) - A. S. Pisaryuk; V. A. Zamarashkina; N. B. Safarova; N. M. Povalyaev; E. O. Kotova; U. I. Babukhina; E. M. Koltsova; Zh. D. Kobalava (Рациональная фармакотерапия в кардиологии, 2022)
The issue of antithrombotic therapy in patients with infective endocarditis has been studied for over 75 years. During that time studying of pathogenesis of the disease and its embolic complications, lead to the introduction of the concept of “immunothrombosis”. That mechanism allows infective agents (mostly bacteria) to be cloaked from the immune system and to multiply freely, leading to growth of vegetation, thus resulting in higher chance of fragmentation. Small-scale experimental and clinical studies on the correction of hemostatic disorders in infective endocarditis, that were performed in 20th century, didn’t show any significant results, that could affect clinical practice. However, reinterpretation of available data on coagulative system will allow to have elements of hemostasis as an application point in treating infective endocarditis. The article will discuss latest insights on the role of hemostasis system in pathophysisology of infective endocarditis, its effects on the development of the embolic complications, perspectives for diagnostics and treatment.